Phosphorus-doped hard carbon composite material and preparation method and application thereof

By doping phosphorus elements in hard carbon composite materials, improving its specific surface area and carbon layer spacing, the problem of low initial Coulomb efficiency is solved, and a higher reversible discharge specific capacity and first Coulomb efficiency are achieved.

CN119650614AActive Publication Date: 2025-03-18碳一(安徽)钠电材料有限公司
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411604960.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-18
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The initial Coulombic efficiency of hard carbon composites limits the performance of sodium ion batteries.

Method used

By doping phosphorus elements, a phosphorus-doped hard carbon composite material is prepared to improve its specific surface area and carbon layer spacing, and enhance catalytic performance and reversible capacity.

Benefits of technology

The initial Coulombic efficiency of the phosphorus-doped hard carbon composite material is significantly improved, and its reversible discharge specific capacity and first Coulombic efficiency are increased.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650614A_ABST
    Figure CN119650614A_ABST
Patent Text Reader

Abstract

The invention provides a phosphorus-doped hard carbon composite material as well as a preparation method and application thereof. The method comprises the following steps: mixing alginate and phosphate in water, and then adding a calcium salt solution to obtain a gelatinous product; drying the gelatinous product to obtain a precursor material; mixing the precursor material and coal, and performing ball milling to obtain a powder material; the powder material is placed in inert gas, then oxygen-containing gas is introduced, low-temperature carbonization is conducted, the precursor material and coal are co-gasified, and an intermediate product is obtained; and performing high-temperature carbonization on the intermediate product to obtain the phosphorus-doped hard carbon composite material. According to the method provided by the invention, the biomass precursor material rich in phosphorus is firstly prepared, then dried and subjected to ball milling with the coal, then co-gasification is performed in the oxygen-containing gas, and finally high-temperature carbonization is performed, so that the doping amount of the phosphorus element can be increased, and rich closed-pore structures can be synchronously formed; the prepared phosphorus-doped hard carbon composite material has excellent reversible discharge specific capacity and initial coulombic efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of sodium ion batteries, and in particular, relates to a phosphorus-doped hard carbon composite material and a preparation method and application thereof. Background Art

[0002] With the development of the new energy industry, lithium-ion batteries have been widely used in industries such as electric vehicles, but their further development is constrained by a series of key issues such as limited lithium resource reserves and high lithium-ion battery costs.

[0003] Sodium-ion batteries have the advantages of low cost, abundant sodium reserves and wide distribution. As the negative electrode material of sodium-ion batteries, hard carbon has more defects and micropores in its disordered amorphous structure, which can provide more active sodium storage sites in hard carbon composites. At the same time, hard carbon has a larger interlayer spacing, which is conducive to the diffusion of sodium ions, and the structure has high stability during the sodiumation / de-sodiumation process. However, the main problem of hard carbon composites is their inherent low initial Coulomb efficiency.

[0004] The contents of the background technology section are merely the technologies known to the inventors and do not necessarily represent the prior art in the field. Summary of the invention

[0005] The purpose of the present invention is to provide a new phosphorus-doped hard carbon composite material to solve the problem of low initial Coulomb efficiency.

[0006] The first aspect of the present application provides a phosphorus-doped hard carbon composite material, wherein the phosphorus doping amount is 5.5-6.5%; the phosphorus-doped hard carbon composite material satisfies: 4.11≤SSA+(P / (P+C))*d 002 ≤4.53, where SSA is the specific surface area of ​​the phosphorus-doped hard carbon composite material, P / (P+C) is the mass ratio of phosphorus element in the phosphorus-doped hard carbon composite material, and d 002 is the carbon layer spacing of the phosphorus-doped hard carbon composite material.

[0007] Phosphorus doping can inhibit the orderly stacking of graphene layers, increase the specific surface area and provide a large number of active sites. It can also increase the interlayer spacing of carbon materials, thereby improving their catalytic performance and significantly increasing the reversible capacity of hard carbon materials. PC bonds have high electrochemical activity and can participate in redox reactions. The adsorption of alkali metal ions by PC bonds and the reversible redox process of PC bonds during the cycle are both conducive to improving electrochemical performance.

[0008] A high doping amount of phosphorus element can effectively increase the interlayer spacing, promote efficient electron transmission, and effectively improve the initial Coulomb efficiency of phosphorus-doped hard carbon composite materials.

[0009] In some embodiments of the present application, the phosphorus-doped hard carbon composite material satisfies at least one of the following conditions:

[0010] a) The specific surface area of ​​the phosphorus-doped hard carbon composite material is 4.1 to 4.5 cm 2 / g;

[0011] b) the carbon interlayer spacing of the phosphorus-doped hard carbon composite material is ≥0.39 nm;

[0012] c) the average pore size of the phosphorus-doped hard carbon composite material is 3.5 to 7.0 nm;

[0013] d) The total pore volume of the phosphorus-doped hard carbon composite material is 0.4 to 0.5 cm 3 / g, the total pore volume of micropores with a pore size of 0 to 2 nm is ≥ 0.12 cm 3 / g, microporosity ≥ 20%, the phosphorus-doped hard carbon composite material includes closed pores;

[0014] e) the intensity ratio of the amorphous carbon peak and the graphitized carbon peak of the phosphorus-doped hard carbon composite material D / I G It is 2.1 to 2.5.

[0015] The hard carbon negative electrode material that meets any one of the above conditions has better performance.

[0016] The second aspect of the present application provides a method for preparing a phosphorus-doped hard carbon composite material, which comprises the following steps:

[0017] S1: mixing alginate and phosphate in water, and then adding calcium salt solution to obtain a gel-like product;

[0018] S2: drying the gel-like product to obtain a precursor material;

[0019] S3: mixing the precursor material and coal and then ball milling them to obtain a powder material;

[0020] S4: placing the powder material in an inert gas, and then introducing an oxygen-containing gas to perform low-temperature carbonization, so that the precursor material and the coal are co-gasified to obtain an intermediate product;

[0021] S5: Carbonizing the intermediate product at high temperature to obtain the phosphorus-doped hard carbon composite material.

[0022] The method provided in the present application first prepares a phosphorus-rich biomass precursor material, then dries it and ball-mills it with coal, then co-gasifies it in an oxygen-containing gas, and finally performs high-temperature carbonization. This not only increases the doping amount of the phosphorus element, but also simultaneously forms a rich closed-pore structure. The resulting phosphorus-doped hard carbon composite material has excellent reversible discharge specific capacity and first coulombic efficiency.

[0023] In some embodiments of the present application, in step S1, the ratio of the amount of the alginate to the amount of the phosphate is 1:(1-2);

[0024] Optionally, the phosphate is selected from one or more of sodium monohydrogen phosphate, sodium dihydrogen phosphate, and dodecyl phosphate;

[0025] Optionally, the molar concentration of the calcium salt solution is 0.1 to 0.5 mol / L;

[0026] Optionally, the calcium salt is selected from one or more of calcium chloride, calcium gluconate, calcium nitrate, calcium bicarbonate, calcium acetate, calcium hypochlorite, calcium perchlorate, calcium permanganate, and calcium lactate;

[0027] Optionally, the calcium salt solution is added in an amount of 10-20% of the total weight of the alginate, the phosphate and the water;

[0028] Optionally, the alginate and the phosphate are stirred and mixed in water for 10 to 14 hours.

[0029] In this step, alginate and phosphate are uniformly mixed in water and then calcium salt solution is added to generate a gel-like calcium alginate-phosphate compound.

[0030] In some embodiments of the present application, in step S3, the coal is selected from one or more of bituminous coal, anthracite, and lignite;

[0031] Optionally, the ratio of the precursor material to the coal is 1:(2-2.5);

[0032] Optionally, the ball mill has a rotation speed of 150 to 250 r / min and a time of 2 to 4 h.

[0033] In this step, the precursor material and coal are ball-milled and mixed evenly to form a powder material, which is beneficial to the subsequent gasification.

[0034] In some embodiments of the present application, in step S4, the temperature of the low-temperature carbonization is 300-500° C., and the time is 3-6 hours;

[0035] Optionally, the heating rate of the low-temperature carbonization is 1 to 3°C / min;

[0036] Optionally, the oxygen-containing gas is selected from air and / or oxygen;

[0037] Optionally, the flow rate of the oxygen-containing gas is 2 to 10 L / min;

[0038] Optionally, the inert gas is selected from one or more of nitrogen, argon, helium, xenon and radon.

[0039] In this step, the precursor material and coal are carbonized at low temperature under oxygen-containing gas, so that the precursor material and coal are co-gasified. The phosphorus compound of the precursor material decomposes and volatilizes at a relatively low temperature, and phosphorus reacts with Ca and Al in the coal ash mineral components to form Al(PO3)3 and Ca3(PO4)2, which improves the stability of the phosphide and effectively reduces the loss of phosphorus in this process.

[0040] In some embodiments of the present application, in step S5, the high temperature carbonization temperature is 1100-1300° C., and the time is 4-10 h;

[0041] Optionally, the heating rate during the high-temperature carbonization is 3-5°C / min.

[0042] In this step, the intermediate product after gasification is further carbonized at high temperature to obtain a phosphorus-doped hard carbon composite material. Under high temperature conditions, calcium phosphate reacts with silicon in coal with carbon or reducing gas as a reducing agent at high temperature as follows: 2Ca3(PO4)2+6SiO2+10C→6CaSiO3+P4+10CO, etching the surface of the carbon material and volatilizing phosphorus in the form of phosphorus element. In a phosphorus-rich atmosphere, phosphorus doping and the formation of a rich closed-cell structure are simultaneously completed.

[0043] The third aspect of the present application provides a negative electrode sheet, which includes any of the above-mentioned phosphorus-doped hard carbon composite materials, or a phosphorus-doped hard carbon composite material prepared by any of the above-mentioned preparation methods.

[0044] The fourth aspect of the present application provides a sodium ion battery, characterized in that it includes the above-mentioned negative electrode sheet.

[0045] In some embodiments of the present application, the reversible discharge specific capacity of the sodium ion battery is ≥295 mAh / g, and the first coulombic efficiency is ≥90%.

[0046] The sodium ion battery provided in the present application has very good reversible discharge specific capacity and first coulombic efficiency.

[0047] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] The accompanying drawings constituting a part of the present disclosure are used to provide a further understanding of the present disclosure. The illustrative embodiments of the present disclosure and their descriptions are used to explain the present disclosure and do not constitute improper limitations on the present disclosure.

[0049] Figure 1 This is a process flow chart for preparing a phosphorus-doped hard carbon composite material provided in one embodiment of the present application.

[0050] Figure 2 This is a SEM image of the phosphorus-doped hard carbon composite material prepared in one embodiment of the present application, with a magnification of 10000×.

[0051] Figure 3 yes Figure 2 A local enlarged image with a magnification of 30000×. DETAILED DESCRIPTION

[0052] In the following, only some exemplary embodiments are briefly described. As those skilled in the art will appreciate, the described embodiments may be modified in various ways without departing from the spirit or scope of the present invention. Therefore, the drawings and descriptions are considered to be exemplary and non-restrictive in nature.

[0053] The disclosure below provides many different embodiments or examples for implementing the present invention. In order to simplify the disclosure of the present invention, the components and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention. In addition, the present invention can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplicity and clarity, which itself does not indicate the relationship between the various embodiments and / or settings discussed. In addition, the present invention provides various specific examples of processes and materials, but those of ordinary skill in the art can appreciate the application of other processes and / or the use of other materials.

[0054] In addition, unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those generally understood by those of ordinary skill in the art to which the present invention belongs. It will also be understood that terms, such as those defined in commonly used dictionaries, should be interpreted as having a meaning consistent with their meaning in the context of the relevant technology and the present invention, and will not be interpreted in an idealized or overly formal sense unless explicitly defined in this article.

[0055] As used herein, "about" or "approximately" includes the stated value and means within an acceptable range of deviation from the particular value as determined by one skilled in the art, taking into account the measurement in question and the errors associated with the measurement of the particular quantity (i.e., the limitations of the measurement system). For example, "about" can mean within one or more standard deviations, or within ±30%, ±20%, ±10%, or ±5% of the stated value.

[0056] The following is a more detailed description of the specific embodiments of the present invention in conjunction with the accompanying drawings and examples, so that the scheme of the present invention and its advantages in various aspects can be better understood. However, the specific embodiments and examples described below are only for the purpose of illustration, rather than for limiting the present invention.

[0057] The present application provides a phosphorus-doped hard carbon composite material, which is doped with phosphorus. Phosphorus and the carbon matrix form a bond in the form of PC. Phosphorus doping can improve defects and oxygen functional groups, increase the storage capacity of sodium, and thus improve the specific capacity of the phosphorus-doped hard carbon composite material. In the present application, the doping amount of phosphorus in the phosphorus-doped hard carbon composite material is 5.5-6.5%. The high doping amount of phosphorus can effectively increase the interlayer spacing, promote the efficient transmission of electrons, and effectively improve the initial coulomb efficiency of the phosphorus-doped hard carbon composite material. In some specific embodiments, the doping amount of phosphorus can be 5.5%, 5.7%, 5.9%, 6.1%, 6.3% or 6.5%.

[0058] In the present application, the phosphorus-doped hard carbon composite material satisfies: 4.11≤SSA+(P / (P+C))*d 002 |≤4.53, where SSA is the specific surface area of ​​the phosphorus-doped hard carbon composite material, P / (P+C) is the mass ratio of phosphorus in the phosphorus-doped hard carbon composite material (i.e., the doping amount of phosphorus), d 002 is the carbon interlayer spacing of the phosphorus-doped hard carbon composite material. When the specific surface area, carbon interlayer spacing and phosphorus doping amount meet the above requirements, the performance of the phosphorus-doped hard carbon composite material is better.

[0059] Optionally, the specific surface area of ​​the phosphorus-doped hard carbon composite material is 4.1 to 4.5 cm 2 / g. The specific surface area is small, the surface defects are few, and the performance of the phosphorus-doped hard carbon composite material is better. In some specific embodiments, the specific surface area of ​​the phosphorus-doped hard carbon composite material can be 4.1cm 2 / g, 4.2cm 2 / g, 4.3cm 2 / g, 4.4cm 2 / g or 4.5cm 2 / g.

[0060] Optionally, the carbon interlayer spacing d of the phosphorus-doped hard carbon composite material 002 ≥0.039nm. A large carbon interlayer spacing is conducive to providing more sodium storage sites. Further optionally, the carbon interlayer spacing d 002 In some specific embodiments, the carbon layer spacing d 002 It may be 0.039nm, 0.0392nm, 0.0394nm, 0.0396nm, 0.0398nm or 0.040nm.

[0061] Optionally, the average pore size of the phosphorus-doped hard carbon composite material is 3.5 to 7.0 nm. Within this pore size range, the phosphorus-doped hard carbon composite material can have more phosphorus elements, so the performance of the prepared sodium ion battery is better. In some specific embodiments, the average pore size of the phosphorus-doped hard carbon composite material can be 3.5 nm, 4.0 nm, 4.5 nm, 5.0 nm, 5.5 nm, 6.0 nm, 6.5 nm or 7.0 nm.

[0062] Optionally, the phosphorus-doped hard carbon composite material has a rich pore structure with a total pore volume of 0.4 to 0.5 cm 3 Optionally, the total pore volume of micropores (pores with a pore size of 0 to 2 nm) is ≥ 0.12 cm 3 / g, microporosity ≥ 20%. In some specific embodiments, the total pore volume may be 0.40 cm 3 / g, 0.41cm 3 / g, 0.42cm 3 / g, 0.44cm 3 / g, 0.46cm 3 / g, 0.48cm 3 / g or 0.50cm 3 / g. The phosphorus-doped hard carbon composite material includes closed pores, and the closed pore structure can reduce the formation of SEI, and the closed pore structure can provide more sodium ion embedding sites, thereby improving the specific capacity of the phosphorus-doped hard carbon composite material. Optionally, the intensity ratio of the amorphous carbon peak and the graphitized carbon peak of the phosphorus-doped hard carbon composite material is D / I G is 2.1 to 2.5. The graphitization degree is low, showing a higher capacity. In some specific embodiments, I D / I G The value can be 2.1, 2.2, 2.3, 2.4 or 2.5.

[0063] Figure 1 A method for preparing a phosphorus-doped hard carbon composite material provided in an embodiment of the present application is shown, including the following steps S1 to S5.

[0064] S1: Alginate and phosphate are mixed in water, and then calcium salt solution is added to obtain a gel-like product.

[0065] In this step, the alginate and phosphate are mixed in water and then the calcium salt solution is added to form a gel-like alginate calcium-phosphate compound. Optionally, the alginate and phosphate are stirred and mixed in water for 10 to 14 hours to fully stir and mix. In some specific embodiments, the stirring time can be 10 hours, 11 hours, 12 hours, 13 hours or 14 hours.

[0066] In step S1, the ratio of alginate to phosphate is 1:(1-2). In the presence of phosphate, the reaction rate of alginate and calcium salt will not be too fast, so that an ideal gel product can be obtained. In some specific embodiments, the ratio of alginate to phosphate can be 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8 or 1:2.

[0067] Alginate can be selected from one or more of sodium alginate, potassium alginate, magnesium alginate, ammonium alginate, etc. Phosphate can be selected from one or more of sodium monohydrogen phosphate, sodium dihydrogen phosphate, dodecyl phosphate, etc. Calcium salt can be selected from one or more of calcium chloride, calcium gluconate, calcium nitrate, calcium bicarbonate, calcium acetate, calcium hypochlorite, calcium perchlorate, calcium permanganate, calcium lactate, etc.

[0068] Optionally, the molar concentration of the calcium salt solution is 0.1-0.5 mol / L. If the concentration of the calcium salt is too high, the reaction speed of the alginate and the calcium salt is very fast. At the above concentration, a relatively ideal gel product can be obtained. In some specific embodiments, the molar concentration of the calcium salt solution can be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L or 0.5 mol / L.

[0069] Optionally, the calcium salt solution is added in an amount of 10-20% of the total weight of alginate, phosphate and water. In some specific embodiments, the added amount may be 10%, 12%, 14%, 16%, 18% or 20%.

[0070] S2: Drying the gel product to obtain a precursor material.

[0071] This step removes the water in the gel-like product so that it can be ball-milled with coal in the following step. Drying can be carried out by drying.

[0072] S3: The precursor material and coal are mixed and ball-milled to obtain a powder material.

[0073] In this step, the precursor material and coal are ball-milled and mixed evenly, and powder material is made, which is conducive to the subsequent gasification. Coal is cheap and contains a large amount of elements, and has great potential for preparing hard carbon. Optionally, the coal is selected from one or more of bituminous coal, anthracite, and lignite.

[0074] Optionally, the ratio of the precursor material to the coal is 1:(2-2.5). In some specific embodiments, the ratio of the precursor material to the coal may be 1:2, 1:2.1, 1:2.2, 1:2.3, 1:2.4 or 1:2.5.

[0075] Optionally, the ball milling speed is 150-250 r / min, and the time is 2-4 h. In some specific embodiments, the ball milling speed is 150 r / min, 170 r / min, 190 r / min, 210 r / min, 230 r / min or 250 r / min. In some specific embodiments, the ball milling time can be 2 h, 2.5 h, 3 h, 3.5 h or 4 h.

[0076] S4: placing the powder material in an inert gas, and then introducing an oxygen-containing gas to perform low-temperature carbonization, so that the precursor material and coal are co-gasified to obtain an intermediate product.

[0077] In this step, the precursor material and coal are carbonized at low temperature under oxygen-containing gas, so that the precursor material and coal are co-gasified. The phosphorus compound of the precursor material decomposes and volatilizes at a relatively low temperature, and phosphorus reacts with Ca and Al in the coal ash mineral components to form Al(PO3)3 and Ca3(PO4)2, which improves the stability of the phosphide and effectively reduces the loss of phosphorus in this process.

[0078] Optionally, the inert gas is selected from one or more of nitrogen, argon, helium, xenon and radon.

[0079] Optionally, the temperature of low temperature carbonization is 300-500°C, and the time is 3-6h. In some specific embodiments, the temperature of low temperature carbonization may be 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C, 460°C, 480°C or 400°C. In some specific embodiments, the time of low temperature carbonization may be 3h, 3.5h, 4h, 4.5h, 5h, 5.5h or 6h.

[0080] Optionally, the heating rate of the low temperature carbonization is 1-3°C / min. In some specific embodiments, the heating rate of the low temperature carbonization may be 1°C / min, 1.5°C / min, 2°C / min, 2.5°C / min or 3°C / min.

[0081] Optionally, the oxygen-containing gas is selected from air and / or oxygen. Optionally, the flow rate of the oxygen-containing gas is 2 to 10 L / min. In some specific embodiments, the flow rate of the oxygen-containing gas may be 2 L / min, 3 L / min, 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min or 10 L / min.

[0082] S5: Carbonizing the intermediate product at high temperature to obtain a phosphorus-doped hard carbon composite material.

[0083] In this step, the intermediate product after gasification is further carbonized at high temperature to obtain a phosphorus-doped hard carbon composite material. Under high temperature conditions, calcium phosphate reacts with silicon in coal with carbon or reducing gas as a reducing agent at high temperature as follows: 2Ca3(PO4)2+6SiO2+10C→6CaSiO3+P4+10CO, etching the surface of the carbon material and volatilizing phosphorus in the form of phosphorus element. In a phosphorus-rich atmosphere, phosphorus doping and the formation of a rich closed-cell structure are simultaneously completed.

[0084] Optionally, the temperature of high temperature carbonization is 1100-1300°C, and the time is 4-10 hours. In some specific embodiments, the temperature of high temperature carbonization may be 1100°C, 1120°C, 1140°C, 1160°C, 1180°C, 1200°C, 1220°C, 1240°C, 1260°C, 1280°C or 1300°C. In some specific embodiments, the time of high temperature carbonization may be 4h, 5h, 6h, 7h, 8h, 9h or 10h.

[0085] Optionally, the heating rate during high-temperature carbonization is 3 to 5°C / min. Low-temperature carbonization and high-temperature carbonization can be carried out in the same equipment. For example, the powder material is first placed in an inert gas, and then an oxygen-containing gas is introduced to carry out low-temperature carbonization. After completion, the introduction of the oxygen-containing gas is stopped, and the temperature is continued to be raised to the high-temperature carbonization temperature for high-temperature carbonization. In some specific embodiments, the heating rate during high-temperature carbonization can be 3°C / min, 3.5°C / min, 4°C / min, 4.5°C / min or 5°C / min.

[0086] The method provided in the present application first prepares a phosphorus-rich biomass precursor material, then dries it and ball-mills it with coal, then co-gasifies it in an oxygen-containing gas, and finally performs high-temperature carbonization, which can not only increase the doping amount of phosphorus element, but also simultaneously form a rich closed-pore structure.

[0087] The present application further provides a negative electrode sheet, comprising the above-mentioned phosphorus-doped hard carbon composite material or the phosphorus-doped hard carbon composite material prepared by the above-mentioned preparation method.

[0088] The negative electrode sheet generally includes a negative electrode current collector and a negative electrode film layer disposed on the negative electrode current collector, wherein the negative electrode film layer may include the above-mentioned phosphorus-doped hard carbon composite material.

[0089] The current collector may be a metal foil, such as an aluminum foil, a copper foil, etc., preferably a copper foil. The negative electrode film layer may further include a binder, a conductive agent, etc. The binder may be, for example, styrene-butadiene rubber (SBR), polyvinylidene chloride (PVDF), polyacrylic acid (PAA), sodium carboxymethyl cellulose (CMC-Na), sodium alginate, etc. The conductive agent may be, for example, graphene, carbon nanotubes, Ketjen black, conductive carbon black (SP), etc. Optionally, the negative electrode film layer may further include other additives, such as a dispersant (e.g., carboxymethyl cellulose (CMC)), etc.

[0090] The present application also provides a sodium ion battery, which includes the above-mentioned negative electrode sheet. The sodium ion battery also includes a positive electrode sheet, a separator and an electrolyte. The sodium ion battery provided in the present application has very good reversible discharge specific capacity and first coulombic efficiency. Optionally, the reversible discharge specific capacity of the sodium ion battery is ≥295mAh / g, and can even be higher than 300mAh / g. Optionally, the first coulombic efficiency of the sodium ion battery is ≥90%.

[0091] The sodium ion battery of the present application is a secondary battery, which refers to a battery that can be used continuously by activating the active material by charging after the battery is discharged. Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the battery charging and discharging process, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet to play an isolating role. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet.

[0092] The present invention will be described below with reference to specific embodiments. The process condition values ​​taken in the following embodiments and comparative examples are exemplary, and their possible numerical ranges are as shown in the aforementioned summary of the invention. For process parameters not particularly noted, conventional techniques can be used. Unless otherwise specified, reagents and instruments used in the technical scheme provided by the present invention can be purchased from conventional channels or the market. It should be noted that, in the absence of conflict, the features in the embodiments in this application and the embodiments can be combined with each other.

[0093] Example 1

[0094] This embodiment prepares a phosphorus-doped hard carbon composite material, and the specific steps are as follows:

[0095] 1) Take 10g of sodium alginate and 15g of sodium dodecyl phosphate, add 100mL of deionized water, stir at room temperature for 30min, add 5mL of 0.5mol / L CaCl2 solution, and stir to form a gel product; then dry the gel product to obtain a precursor material.

[0096] 2) The precursor material and lignite were mixed in a mass ratio of 1:2.5, and ball-milled at 200 r / min for 3 h to obtain a powder material.

[0097] 3) The powder material is placed in argon gas, and then oxygen is introduced at a flow rate of 8 L / min. The heating rate is 2°C / min, and the temperature is raised to 400°C for low-temperature carbonization, which is kept warm for 6 hours. The oxygen is turned off and the temperature is continued to be raised at a heating rate of 5°C / min. The temperature is raised to 1300°C for high-temperature carbonization, which is kept warm for 4 hours. After cooling, a phosphorus-doped hard carbon composite material is obtained.

[0098] Example 2

[0099] This embodiment prepares a phosphorus-doped hard carbon composite material, and the specific steps are as follows:

[0100] 1) Take 10g of sodium alginate, 10g of sodium monohydrogen phosphate, and 10g of sodium dihydrogen phosphate, add 100mL of deionized water, stir at room temperature for 30min, add 5mL of 0.5mol / L CaCl2 solution, and stir to form a gel product; then dry the gel product to obtain a precursor material.

[0101] 2) The precursor material and bituminous coal were mixed in a mass ratio of 1:2, and ball-milled at 200 r / min for 3 h to obtain a powder material.

[0102] 3) The powder material is placed in argon gas, and then oxygen is introduced at a flow rate of 8 L / min. The heating rate is 2°C / min, and the temperature is raised to 400°C for low-temperature carbonization, which is kept warm for 4 hours. The oxygen is turned off and the temperature is continued to be raised at a heating rate of 5°C / min. The temperature is raised to 1300°C for high-temperature carbonization, which is kept warm for 4 hours. After cooling, a phosphorus-doped hard carbon composite material is obtained.

[0103] Example 3

[0104] This embodiment prepares a phosphorus-doped hard carbon composite material, and the specific steps are as follows:

[0105] 1) Take 10g of potassium alginate, 10g of sodium monohydrogen phosphate, and 10g of sodium dihydrogen phosphate, add 100mL of deionized water, stir at room temperature for 30min, add 5mL of 0.5mol / L Ca(NO3)2 solution, and stir to form a gel product; then dry the gel product to obtain a precursor material.

[0106] 2) The precursor material and anthracite were mixed in a mass ratio of 1:2, and ball-milled at 200 r / min for 3 h to obtain a powder material.

[0107] 3) The powder material is placed in argon gas, and then oxygen is introduced at a flow rate of 8 L / min. The heating rate is 2°C / min, and the temperature is raised to 400°C for low-temperature carbonization, which is kept warm for 4 hours. The oxygen is turned off and the temperature is continued to be raised at a heating rate of 5°C / min. The temperature is raised to 1300°C for high-temperature carbonization, which is kept warm for 4 hours. After cooling, a phosphorus-doped hard carbon composite material is obtained.

[0108] Example 4

[0109] This embodiment prepares a phosphorus-doped hard carbon composite material, and the specific steps are as follows:

[0110] 1) Take 10g of sodium alginate and 15g of sodium dodecyl phosphate, add 100mL of deionized water, stir at room temperature for 30min, add 5mL of 0.5mol / L CaCl2 solution, and stir to form a gel product; then dry the gel product to obtain a precursor material.

[0111] 2) The precursor material and lignite were mixed in a mass ratio of 1:2.5, and ball-milled at 200 r / min for 3 h to obtain a powder material.

[0112] 3) The powder material is placed in argon gas, and then oxygen is introduced at a flow rate of 4 L / min. The heating rate is 2°C / min, and the temperature is raised to 300°C for low-temperature carbonization, which is kept warm for 6 hours. The oxygen is turned off and the temperature is continued to be raised at a heating rate of 5°C / min. The temperature is raised to 1300°C for high-temperature carbonization, which is kept warm for 4 hours. After cooling, a phosphorus-doped hard carbon composite material is obtained.

[0113] Example 5

[0114] This embodiment prepares a phosphorus-doped hard carbon composite material, and the specific steps are as follows:

[0115] 1) Take 10g of sodium alginate and 20g of sodium monohydrogen phosphate, add 100mL of deionized water, stir at room temperature for 30min, add 5mL of 0.5mol / L CaCl2 solution, and stir to form a gel product; then dry the gel product to obtain a precursor material.

[0116] 2) The precursor material and lignite were mixed in a mass ratio of 1:2.5, and ball-milled at 400 r / min for 3 h to obtain a powder material.

[0117] 3) The powder material is placed in argon gas, and then oxygen is introduced at a flow rate of 4 L / min. The heating rate is 2°C / min, and the temperature is raised to 400°C for low-temperature carbonization, which is kept warm for 6 hours. The oxygen is turned off and the temperature is continued to be raised at a heating rate of 5°C / min. The temperature is raised to 1200°C for high-temperature carbonization, which is kept warm for 6 hours. After cooling, a phosphorus-doped hard carbon composite material is obtained.

[0118] Example 6

[0119] This embodiment prepares a phosphorus-doped hard carbon composite material, and the specific steps are as follows:

[0120] 1) Take 10g of sodium alginate and 15g of sodium dodecyl phosphate, add 100mL of deionized water, stir at room temperature for 30min, add 5mL of 0.5mol / L CaCl2 solution, and stir to form a gel product; then dry the gel product to obtain a precursor material.

[0121] 2) The precursor material and lignite were mixed in a mass ratio of 1:2.5, and ball-milled at 400 r / min for 3 h to obtain a powder material.

[0122] 3) The powder material is placed in argon gas, and then oxygen is introduced at a flow rate of 8 L / min. The heating rate is 1°C / min, and the temperature is raised to 400°C for low-temperature carbonization, which is kept warm for 6 hours. The oxygen is turned off and the temperature is continued to be raised at a heating rate of 3°C / min. The temperature is raised to 1200°C for high-temperature carbonization, which is kept warm for 6 hours. After cooling, a phosphorus-doped hard carbon composite material is obtained.

[0123] Comparative Example 1

[0124] The difference between this comparative example and Example 1 is that the lignite in step 2) is replaced by coconut shell.

[0125] Comparative Example 2

[0126] The difference between this comparative example and Example 1 is that sodium lauryl phosphate is not added in step 1).

[0127] Comparative Example 3

[0128] The difference between this comparative example and Example 1 is that no sodium alginate is added in step 1).

[0129] Comparative Example 4

[0130] The difference between this comparative example and Example 1 is that in step 2), the precursor material and the lignite are not ball-milled, and step 3) is directly performed after mixing.

[0131] Comparative Example 5

[0132] The difference between this comparative example and Example 1 is that in step 3), no oxygen is introduced and low-temperature carbonization is performed in argon gas.

[0133] Comparative Example 6

[0134] The difference between this comparative example and Example 1 is that in step 3), after oxygen is introduced, low-temperature carbonization is not performed but high-temperature carbonization is performed directly.

[0135] Test Example 1

[0136] The phosphorus-doped hard carbon composite materials of Examples 1 to 6 and Comparative Examples 1 to 6 were subjected to N2 adsorption and desorption to detect the specific surface area. The specific surface area and pore structure were determined by gas adsorption method, and the carbon layer spacing d was determined by XRD. 002 Calculate the wavelength of the incident light. The intensity ratio of the typical D peak and G peak to the intensity of the amorphous carbon peak and the graphitized carbon peak was measured by Raman spectroscopy. D / I G The phosphorus (P) content in the material was determined using an organic element analyzer (EA). The results are shown in Table 1.

[0137] The SEM image of the phosphorus-doped hard carbon composite material prepared in Example 1 is shown in Figure 2 and Figure 3 ,in Figure 2 The magnification is 10000×. Figure 3 for Figure 2 A local enlarged image with a magnification of 30000×.

[0138] Table 1

[0139]

[0140] It can be seen from Examples 1 to 6 and Comparative Examples 1 to 6 in Table 1 that the use of alginate and phosphate compounding can effectively increase the phosphorus doping amount in the subsequently prepared phosphorus-doped hard carbon composite material. When other biomass that is difficult to compound phosphorus is used for doping, and when phosphate and alginate are not added for mixing, the phosphorus doping amount of the subsequently prepared phosphorus-doped hard carbon composite material is significantly reduced, which is not conducive to the increase of the interlayer spacing after carbonization. For the precursor that is not mixed with coal, phosphorus escapes at a low temperature, and the subsequent phosphorus doping amount is reduced. Failure to perform ball milling results in uneven material mixing, which is not conducive to the release of phosphorus during the subsequent carbonization process. The specific surface area of ​​the prepared phosphorus-doped hard carbon composite material is relatively large, and the phosphorus doping amount is low. In the subsequent two-stage heating, the first stage of carbonization is carried out in an oxygen-containing atmosphere. On the one hand, the coal can be pre-oxidized and cross-linked. On the other hand, under the action of low temperature, the escaped phosphorus element can be effectively captured by Ca and Al in the coal to form calcium phosphate and aluminum phosphate, which can effectively increase the phosphorus doping amount of the subsequently prepared hard carbon.

[0141] Test Example 2

[0142] The phosphorus-doped hard carbon composite materials obtained in Examples 1 to 6 and Comparative Examples 1 to 6 were used as negative electrode materials to prepare sodium ion batteries according to the following methods. The method for preparing a button-type sodium ion battery comprises the following steps:

[0143] According to the ratio of active material: SP: CMC: SBR = 94: 2: 1.5: 2.5, weigh the negative electrode material, SP, CMC, and SBR respectively, mix them evenly in deionized water to prepare slurry; apply the mixed slurry on the aluminum foil current collector, bake it in an oven at 80°C for 1h, and take it out and cool it to room temperature;

[0144] Adjust the rolling distance to roll the pole piece. Cut the rolled pole piece into small discs with a diameter of 14 mm and weigh them as m1. Similarly, cut the aluminum foil current collector into aluminum foil discs with a diameter of 14 mm and weigh them as m2. (m1-m2)*0.94 is the mass of the active material, recorded as m3. The weighed small discs are then placed in an 80°C oven and vacuum-dried for 12 hours.

[0145] The vacuum-dried small disc was transferred to a glove box, and a sodium ion button cell was assembled in a glove box with oxygen and water content less than 0.01 ppm, using a sodium sheet as a counter electrode and an auxiliary electrode, an electrolyte of 1 M NaPF6 / EC:DMC:DEC=2:2:1, and a glass fiber diaphragm as a diaphragm. The assembled button sodium ion battery was left to rest for 12 hours.

[0146] The static button-type sodium ion battery was tested for electrochemical performance at constant current on the Wuhan Blue Electric Battery Test System. The test results are shown in Table 2.

[0147] Table 2

[0148]

[0149] As can be seen from Table 2, the electrochemical performance of the hard carbon prepared later can be effectively improved by mixing the phosphorus-rich precursor material with coal and then carbonizing it in an oxygen-containing gas. When the phosphorus-containing biomass precursor is added and low-temperature carbonization is performed, the phosphorus compound decomposes and volatilizes at a relatively low temperature, and forms calcium phosphate and aluminum phosphate with Ca and Al in the coal ash mineral components and is captured. After the oxygen-containing gas is stopped, the temperature is continued to be raised for high-temperature carbonization. Under high temperature conditions, calcium phosphate reacts with silicon with carbon or reducing gas as a reducing agent to etch the surface of the carbon material, and at the same time, inorganic phosphorus is volatilized in the form of phosphorus alone. In a phosphorus-rich atmosphere, phosphorus doping and the formation of a rich closed-cell structure are completed simultaneously. For the precursor that is not mixed with coal, phosphorus escapes at a low temperature, reducing the subsequent phosphorus doping amount. Ball milling can effectively increase the consistency of the coal and the precursor after mixing, and is also conducive to the occurrence of subsequent reactions. The phosphorus-doped hard carbon composite material prepared by this method has a small specific surface area, and excellent reversible discharge specific capacity and first coulomb efficiency.

[0150] Obviously, the above embodiments are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the protection scope of the present invention.

Claims

1. A phosphorus-doped hard carbon composite material, characterized in that: The phosphorus doping amount of the phosphorus doped hard carbon composite material is 5.5-6.5%; the phosphorus doped hard carbon composite material satisfies: 4.11≤SSA+(P / (P+C))*d 002 ≤4.53, where SSA is the specific surface area of ​​the phosphorus-doped hard carbon composite material, P / (P+C) is the mass ratio of phosphorus element in the phosphorus-doped hard carbon composite material, and d 002 is the carbon layer spacing of the phosphorus-doped hard carbon composite material.

2. The phosphorus-doped hard carbon composite material according to claim 1, characterized in that: The phosphorus-doped hard carbon composite material satisfies at least one of the following conditions: a) The specific surface area SSA of the phosphorus-doped hard carbon composite material is 4.1 to 4.5 cm 2 / g; b) The carbon interlayer spacing d of the phosphorus-doped hard carbon composite material 002 ≥0.39nm; c) the average pore size of the phosphorus-doped hard carbon composite material is 3.5 to 7.0 nm; d) The total pore volume of the phosphorus-doped hard carbon composite material is 0.4 to 0.5 cm 3 / g, the total pore volume of micropores with a pore size of 0 to 2 nm is ≥ 0.12 cm 3 / g, microporosity ≥ 20%, the phosphorus-doped hard carbon composite material includes closed pores; e) the intensity ratio of the amorphous carbon peak and the graphitized carbon peak of the phosphorus-doped hard carbon composite material D / I G It is 2.1 to 2.

5.

3. A method for preparing a phosphorus-doped hard carbon composite material, characterized in that: The steps include: S1: mixing alginate and phosphate in water, and then adding calcium salt solution to obtain a gel-like product; S2: drying the gel-like product to obtain a precursor material; S3: mixing the precursor material and coal and then ball milling them to obtain a powder material; S4: placing the powder material in an inert gas, and then introducing an oxygen-containing gas to perform low-temperature carbonization, so that the precursor material and the coal are co-gasified to obtain an intermediate product; S5: Carbonizing the intermediate product at high temperature to obtain the phosphorus-doped hard carbon composite material.

4. The preparation method according to claim 3, characterized in that: In step S1, the ratio of the alginate to the phosphate is 1:(1-2); Optionally, the phosphate is selected from one or more of sodium monohydrogen phosphate, sodium dihydrogen phosphate, and dodecyl phosphate; Optionally, the molar concentration of the calcium salt solution is 0.1 to 0.5 mol / L; Optionally, the calcium salt solution is added in an amount of 10-20% of the total weight of the alginate, the phosphate and water; Optionally, the calcium salt is selected from one or more of calcium chloride, calcium gluconate, calcium nitrate, calcium bicarbonate, calcium acetate, calcium hypochlorite, calcium perchlorate, calcium permanganate, and calcium lactate; Optionally, the alginate and the phosphate are stirred and mixed in water for 10 to 14 hours.

5. The preparation method according to claim 3, characterized in that: In step S3, the coal is selected from one or more of bituminous coal, anthracite, and lignite; Optionally, the ratio of the precursor material to the coal is 1:(2-2.5); Optionally, the ball mill has a rotation speed of 150 to 250 r / min and a time of 2 to 4 h.

6. The preparation method according to claim 3, characterized in that: In step S4, the low-temperature carbonization temperature is 300-500° C. and the time is 3-6 hours; Optionally, the heating rate of the low-temperature carbonization is 1 to 3°C / min; Optionally, the oxygen-containing gas is selected from air and / or oxygen; Optionally, the flow rate of the oxygen-containing gas is 2 to 10 L / min; Optionally, the inert gas is selected from one or more of nitrogen, argon, helium, xenon and radon.

7. The preparation method according to claim 3, characterized in that: In step S5, the high temperature carbonization temperature is 1100-1300°C and the time is 4-10 hours; Optionally, the heating rate during the high-temperature carbonization is 3-5°C / min.

8. A negative electrode sheet, characterized in that: The invention comprises the phosphorus-doped hard carbon composite material as claimed in claim 1 or 2, or the phosphorus-doped hard carbon composite material prepared by the preparation method as claimed in any one of claims 3 to 7.

9. A sodium ion battery, characterized in that: Includes the negative electrode sheet as described in claim 8.

10. The sodium ion battery according to claim 9, characterized in that: The reversible discharge specific capacity of the sodium ion battery is ≥295 mAh / g, and the first coulombic efficiency is ≥90%.

Citation Information

Patent Citations

  • Hard carbon material and preparation method and application thereof

    CN115849337A

  • Natural polysaccharide-based hard carbon material as well as preparation method and application thereof

    CN118039898A

  • Hard carbon composite material and preparation method and application thereof

    CN118248874A

  • Negative electrode material and preparation method and application thereof

    CN118398811A